Strategi Pembelajaran Seni Tari Di SMA Negeri 8 Kota Padang - Nanda Laras Saskia; Yuliasma Yuliasma (FBS Universitas Negeri Padang, 2021)
This research aims to find out and describe the strategies used in the learning of dance arts at Sma Negeri 8 Padang. This research is a type of qualitative research with a descriptive approach to analysis. The object of this study is and Mrs. Yetnimasnen, S.Pd. and students of class X IPA 3 Sma Negeri 8 Padang numbering 40 people using primary and secondary data types. The data collection techniques used in this study use library study techniques, interviews, observations, and documentation. The technical data analysis in this study is to identify data, classify data, clarify data, describe data, analyze data, and conclude. The result of this study is that cultural arts teachers do not apply learning strategies in accordance with the design of learning implementation (RPP) on the implementation of dance arts learning, this has an impact on students' learning outcomes that are less good and the learning atmosphere is less conducive and not interactive. Learning strategies that are not appropriate, affect the evaluation of learners who have not been able to achieve KD and the learning goals that have been set.